Some remarks on the generalization of orthogonality in terms of operators - Ojha, B. P.; Bajracharya, P. M. (Methods of Functional Analysis and Topology, 2021)
This paper deals with a generalization of orthogonality in terms of bounded linear operators on a Banach space. The goal is to find a relation between orthogonality of images and orthogonality of elements. We prove that if the images of a bounded linear operator are orthogonal in the Pythagorean sense, then the elements are orthogonal in the sense of Birkhoff’s definition. In the case of Robert’s orthogonality in terms of bounded linear operators under the restriction that any element belongs to the intersection of the norm attainment set of T_1+λ T_2 and T_1-λ T_2, if the images are orthogonal, then it implies that the operators are also orthogonal. Furthermore, some results in relation to the Carlsson, isosceles, and approximate Birkhoff-James orthogonality have been obtained. У цій роботі розглядяється узагальнення ортогональності в термінах обмежених лінійних операторів на банаховому просторі. Метою роботи є знайти співвідношення між ортогональністю зображень і ортогональністю елементів. Доведено, що якщо образи обмеженого лінійного оператора ортогональні в піфагоровому сенсі, то елементи є ортогональний у сенсі визначення Біркгофа. У випадку ортогональності Роберта в термінах обмежених лінійних операторів із умовою, що будь-який елемент належить до перетину множин де оператори T_1+λ T_2 і T_1-λ T_2 досягають норми, з ортогональності образів випливає, що оператори є також ортогональні. Також отримано деякі результати про ортогональність в сенсі Карлссона, рівнобічної ортогональності та наближеної ортогональності в сенсі Біркгофа-Джеймса.